Banking and finance issues in emerging markets - Barnett, William A.; Sergi, Bruno S. (International symposia in economic theory and econometrics ;, 2018)
The banking and finance sectors are relevant shares of modern economies and indeed drivers of growth in emerging economies. The majority of existing economic and finance textbooks focus on concepts and theories with briefly exposited real-world examples for illustration. This book, which collects chapters that are the contributions of the acknowledged experts in their fields, fills this gap by featuring in-depth analyses on prominent real-world topics in banking and finance. The book's applications of econometrics present insightful perspectives on the recent development of banking issues, stock market contagion, the impact of internet technology (IT) on stock markets, financial innovation and technology firms, and an international perspective on the loan puzzle and interest rate adjustment in emerging markets. In addition to exhaustive case studies on banking and finance in India, Hong Kong, Japan, and other Asian emerging markets, the authors coherently contribute an intellectual advancement of contemporary issues in banking and finance literature. The authors offer an essential reading and source of reference for postgraduate and advanced undergraduate courses in economics and finance.